Expression and functional roles of estrogen receptor GPR30 in human intervertebral disc. Issue 158 (April 2016) - Wei, Aiqun; Shen, Bojiang; Williams, Lisa A.; Bhargav, Divya; Yan, Feng; Chong, Beng H.; Diwan, Ashish D.
Graphical abstract: Highlights: GPR30 is expressed in nucleus pulposus of human intervertebral disc. GPR30 is expressed in human fetal nucleus pulposus at 12–14 weeks of gestation. Both GPR30 and ER are required for E2 mediated NP cell proliferation and survival. Abstract: Estrogen withdrawal, a characteristic of female aging, is associated with age-related intervertebral disc (IVD) degeneration. The function of estrogen is mediated by two classic nuclear receptors, estrogen receptor (ER)-α and -β, and a membrane bound G-protein-coupled receptor 30 (GPR30). To date, the expression and function of GPR30 in human spine is poorly understood. This study aimed to evaluate GPR30 expression in IVD, and its role in estrogen-related regulation of proliferation and apoptosis of disc nucleus pulposus (NP) cells. GPR30 expression was examined in 30 human adult NP and 9 fetal IVD. Results showed that GPR30 was expressed in NP cells at both mRNA and protein levels. In human fetal IVD, GPR30 protein was expressed in the NP at 12–14 weeks gestation, but was undetectable at 8–11 weeks. The effect of 17β-estradiol (E2) on GPR30-mediated proliferation and interleukin-1β (IL-1β)-induced apoptosis of NP cells was investigated. Cultured NP cells were treated with or without E2, GPR30 antagonist G36, and ER antagonist ICI 182, 780. NP cell viability was tested by MTS assay. Apoptosis was determined by flow cytometry using fluorescence labeled annexin-V, TUNEL assay and immumnocytochemical staining of activated caspase-3. E2 enhanced cell proliferation and prevented IL-1β-induced cell death, but the effect was partially blocked by G36 and completely abrogated by a combination of ICI 182, 780 and G36. This study demonstrates that GPR30 is expressed in human IVD to transmit signals triggering E2-induced NP cell proliferation and protecting against IL-1β-induced apoptosis. The effects of E2 on NP cells require both GPR30 and classic estrogen receptors.